Associative learning alone is insufficient for the evolution and maintenance of the human mirror neuron system. Issue 2 (29th April 2014) - Oberman, Lindsay M.; Hubbard, Edward M.; McCleery, Joseph P.
Abstract Cook et al. argue that mirror neurons originate from associative learning processes, without evolutionary influence from social-cognitive mechanisms. We disagree with this claim and present arguments based upon cross-species comparisons, EEG findings, and developmental neuroscience that the evolution of mirror neurons is most likely driven simultaneously and interactively by evolutionarily adaptive psychological mechanisms and lower-level biological mechanisms that support them.